PENGARUH TERAPI STOP BERPIKIR NEGATIF TERHADAP KETERGANTUNGAN NARKOBA DI PANTI REHABILITASI NARKOBA RUMAH DAMAI GUNUNG PATI SEMARANG - Sri Endang Windiarti; - Indriti; Fajar Surachmi (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2013)
Drug abuse is a nat ional problem at the moment and has been linked with crime, unemployment, health and economy. Drug abuse begins most ly in adolescence. Causes of drug abuse is mult ifactorial. In the case of drug addiction which one is the effect of the subconscious urge to continuetaking drugs, compared wit h the needs of the body to chemicals in drugs. Therapeutic stop negative thinking is one of the treatments to overcome personal and psychological problems for drug dependence. The purpose of this study was to determine the effect of therapy stop thinking negativelyagainst drug addiction in Rehabilitation Orphanage  Rumah Damai Gunung  Pati Semarang.  This metode of research used in this research is quasy experiment with pretest - posttes  without the control group design. Samples taken in this study is the total sampling. The patient's drug dependence in Rumah Damai approximately 50 people. The eligible studywere 30 respondents. Results of analysis of the t value is equal to 4829 with the sig 0000. Because the sig <0.05, it can be concluded that H1 is accepted, it means stop thinking negative therapy before and after the behavior of drug addiction there are differences, so it can be stated that the therapy stop thinking negatively influence behavior dependence.This study can be resumed wit h another therapeutic model, in order to improve government programs, communities and families to reduce drug dependency problems.Keywords:Thinking,Negative,Drugs